Use of Fever and Pain Medication for Self-Medication at the Talita Pharmacy, Makassar City - Asrina, Rina; Hasyim, Muhammad Farid; Yogi, Yogi (Jurnal Farmasi Sandi Karsa, 2022)
Self-medication is part of "self-care" which is an effort to maintain health or prevent and overcome disease. Self-medication is usually done to treat minor illnesses, including fever and pain. The purpose of this study was to find out which class of Fever and Pain drugs were most widely used for self-medication at the Talita Pharmacy, Makassar City. This research method has used descriptive method. The results showed that the most widely used Fever and Pain drug group in January was paracetamol as much as 85.1851%, February as much as 72.27%, March as much as 0.8088%. So it can be concluded that the most widely used class of fever and pain drugs for self-medication at the Talita Pharmacy in Makassar City in January - March 2022 is the Acetaminophen (Paracetamol) group.